Annals of Palliative Medicine (APM) is going to publish bi-monthly starting in September 2019! - Office, Editorial (Annals of Palliative Medicine; Vol 8, No 4 (September 27, 2019): Annals of Palliative Medicine, 2019)
Since its launch in 2012, Annals of Palliative Medicine (APM) has been published quarterly with both online and printed copies. With the journal receiving its first official impact factor earlier this year (1), submissions to APM has been rapidly increasing. This is a reflection of the ever-increasing recognition of APM and continuing support by our authors. As a high-quality academic exchange platform, we would like to assist more and more clinicians and researchers in showcasing their scientific achievements. We are also committed to publishing articles quickly, allowing for impactful and potentially practice-changing articles to be available to readers soon after acceptance. Therefore, we are delighted to inform you that the APM will begin bi-monthly publications beginning in September 2019. The regular publication months will be January, March, May, July, September and November.